ANALISIS FAKTOR RISIKO GANGGUAN MUSKULOSKELETAL PADA PENGAYUH BECAK (STUDI KASUS DI PASAR PAGI KABUPATEN PEMALANG) - Esti Mukaromah; Suroto Suroto; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
Occupational disease caused by unergonomically designed workstations are Musculoskeletal Disorders. One of profession in informal sector of transportation services which still used the role of human labor is pedicab driver. That kinds of profession has high risk on its workers towards the occurance of body parts injury or skeletal muscle. Pedicab driver who works in the market is not only carry passengers but also carry goods market. This study aim is to analyze the risk factor of Musculoskeletal Disorders on pedicab drivers (A Case Study of Pasar Pagi in Pemalang Regency). This type of research is descriptive with qualitative approach and observation. The subject of the research were five people. Triangulation in this study is the assessment results of Rapid Entire Body Assessment (REBA) method and field observation. The result of this research showed that the risk factor of paddling activity most affected was the awkward posture on the wrist, back, and legs with repetitive movements 40times/minute, long duration, and high workload. While the the risk factor of lifting the loads most affected was the awkward posture on the neck, shoulder, wrist, back, and legs, repetitive motion 3-8 times, lifting the loads about 5-25 kg in one lift, long duration, and required a great of energy. All of five informants were male, in the age range between 42-60 years old, with the longest work period 32 years. The researcher suggests to the pedicab drivers to do stretching in a limb during working time.